Examining the Effect of Leader–Member Exchange Social Comparison on Employee Voice Behavior: The Role of Employee–Organization and Supervisors Organizational Embodiment - Kumar, Shalendra S; Kang, Shinhyung (International Journal of Management and Sustainability, 2021)
Drawing on social comparison theory (SCT), this research aims to explore the moderated path by testing the interaction effect of a supervisor’s organizational embodiment between leader–member exchange social comparison and employee voice behavior (EVB), as well as the mediating role of the employee–organization relationship (EOR). The hypothesis was tested based on the moderated mediation model using a sample of 788 employees through a structured questionnaire from public sector organizations in Fiji. The findings of the study showed that leader–member exchange social comparison (LMXSC) are positively related to employee voice behavior. Furthermore, the mediating role of the employee–organization relationship quality had significantly strengthened the relationship. In addition, supervisors’ organizational embodiment (SOE) also positively moderated the influence of LMXSC on EVB, and LMXSC on EOR quality. This research delineates the brighter side of social comparison, suggesting that employee voice behavior can be enhanced through fair distribution of the leaders’ resources among the employees, communication training, two-way interactive communication, and employee empowerment in improving work ethics and creating a sustainable organization. Finally, to lead an organization ethically, managers need to encourage voicing behavior of subordinates. Employees need to stand up against unethical issues to enhance the social responsibility of the corporation. The limitations and directions for the future are also presented.